Differences Effectiveness of Percutaneous Nephrolithotomy and Open Surgery in Staghorn Stone Patients: Systematic Review - Ramandita Duta Dewangga; Tarmono Djojodimedjo; Dyah Erawati (Health Notions, 2020)
This study purpose to analyze the differences in the effectiveness of PCNL and open surgery in patients with staghorn stones. We searched the literatures from PubMed and ScienceDirect from year 2005 until 2020. The method used in this study was a systematic review with a quantitative statistical approach (meta-analysis) using primary research data. From 4 studies there were 148 cases of PCNL and 98 cases of open surgery. PCNL had lower postoperative stone-free rate than open surgery (OR 0.168). PCNL had a lower final stone-free rate than open surgery (OR 0.603). The number of patients who had complications with PCNL was lower than open surgery (OR 0.451). The number of patients receiving blood transfusions on PCNL was lower than for open surgery (OR 0.494). Patients who received PCNL procedure required a shorter hospital stay than open surgery (MD -3,234). The number of patients who received additional therapy modalities on PCNL was lower than open surgery (OR 1.917). The conclusions obtained in this study indicate that there are differences in the effectiveness of PCNL and open surgery for patients with staghorn stones. Keywords: percutaneous nephrolithotomy; open surgery; staghorn stone